AN ANALYTICAL STUDY ON EFFECTIVENESS OF INFOGRAPHICS IN INDIAN ENGLISH NEWSPAPERS - Kumar, Abha S; Babu, S.Dinesh (International Journal of Psychosocial Rehabilitation, 2020)
Interactive info graphics are increasingly used in online journalism. Info graphics is representation of data and information. There are several software applications and tools are available to create attractive and informative infographics. It is widely used in educational content, web site portals, news channels and newspaper. With changing life-styles in a world of information that make news quickly and easier using infographics which come to audience in a short, clear and visually attractive manner. Media wants to consume much more information and attract readers to the news content and here infographics plays a vital role. The paper aims to give an analysis of the effectiveness of infographics used in newspapers. Four Indian English newspapers were selected for the study. Also analysing which category of news contents are often used for infographics. The study explores the visualisers perceptions towards info graphical elements. Main tools for data collection are surveys. The results of the reader survey demonstrate how readers interactive with infographics.